Photonic Microresonator Research and Applications - Chremmos, Ioannis; Schwelb, Otto.; Uzunoglu, Nikolaos; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Photonic Microresonator Research and Applications explores advances in the fabrication process that enable nanometer waveguide separations. The technology surrounding the design and fabrication of optical microresonators has matured to a point where there is a need for commercialization. Consequently, there is a need for device research involving more advanced architectures and more esoteric operating princples. This volume discusses these issues, while also: Showing a reader how to design and fabricate microresonators Discussing microresonators in photonic crystals, microsphere circuits, and sensors, and provides application oriented examples Covering the latest in microresonator research with contributions from the leading researchers Photonic Microresonator Research and Applications would appeal to researchers and academics working in the optical sciences.
Fundamental Principles of Operation and Notes on Fabrication of Photonic Microresonators -- Circular Integrated Optical Microresonators: Analytical Methods and Computational Aspects -- Polarization Rotation in Ring Resonators -- Series-Coupled and Parallel-Coupled Add/Drop Filters and FSR Extension -- Advanced Microring Photonic Filter Design -- Band-Limited Microresonator Reflectors and Mirror Structures -- Slow and Stopped Light in Coupled Resonator Systems -- Processing Light in Reconfigurable Directly Coupled Ring Resonators -- Microresonators with Active Tuning -- Performance of Single and Coupled Microresonators in Photonic Switching Schemes -- Single Molecule Detection Using Optical Microcavities -- Microfiber and Microcoil Resonators and Resonant Sensors -- Photonic Crystal Ring Resonators and Ring Resonator Circuits -- High-Q Photonic Crystal Microcavities -- Radial Bragg Resonators -- Photonic Molecules and Spectral Engineering -- Fundamentals and Applications of Microsphere Resonator Circuits -- MEMS-Tuned Microresonators -- Microresonators for Communication and Signal Processing Applications.
Keywords: Engineering; Microwaves; Electronics; Engineering; Electronics and Microelectronics, Instrumentation; Laser Technology, Photonics; Optics, Optoelectronics, Plasmonics and Optical Devices; Microwaves, RF and Optical Engineering